The Influence of Moving and Fixed Target Training Methods, Eye-Foot Coordination on the Accuracy of Passing Soccer (UIR Football School Age-16) - Alficandra, Alficandra; Yani , Ahmad; Thomas , Angga (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. This study was to analyze the method of passing training with fixed target eye-foot coordination high-low and target passing moving eye-foot coordination high-low and analyze the interaction between passing training methods and eye-foot coordination on football passing accuracy. Materials and methods. This study used a quasi-experimental method of pre-test and post-test design. The population in this study was 36 players with an average age of 16 years. The sampling technique used was total sampling with a total sample of 36 players, data analysis used the ANOVA test. Results. 1) There is a difference in the effect between fixed target passing practice and moving target passing on football passing accuracy on average p = (82.78±7.51), p-value = (0.000<0.05) and Fcount ( 18,050)>Ftable (0.225). 2) There is a different effect between high and low eye-foot coordination on soccer passing accuracy where the value of sig p-value = (0.007 <0.05) and Fcount (8.450)>Ftable (0.225). 3) There is a difference in the Effect of Fixed Target Passing Training Method with High and Low Eye-foot Coordination on Soccer Passing Accuracy with an average value of p = (83.33> 67.78). 4) There is a difference in the effect of moving target passing practice with high and low eye-foot coordination on soccer passing accuracy with an average value of p=(85.56>80.00). 5) There is no interaction between training methods and eye-foot coordination on football passing accuracy with sig p-value = (0.053>0.05) and Fcount (4.050) >Ftable (0.225). Conclusions. Research shows that moving target passing exercises are better at improving passing accuracy than fixed target passing exercises and players with high eye-foot coordination have better accuracy than players with low eye-foot coordination.